The product-controllable aerobic oxidative cleavage of vicinal diols using vanadium-based photocatalysts. Issue 5 (4th February 2022) - Yang, Guobao; Shi, Jing; Sun, Haijing; Tong, Xinli
Abstract : A method for the photocatalytic controllable oxidative cleavage of C–C bonds is developed with molecular oxygen as the oxidant. Abstract : A method for the photocatalytic controllable oxidative cleavage of C–C bonds is developed with molecular oxygen as the oxidant. Herein, a series of vanadium-oxide-based photocatalysts was synthesized and characterized via XPS, PL, EIS, BET, and SEM techniques. During the oxidative cleavage of vicinal diols, the main-product selectivity can be greatly regulated based on the used catalyst system. For instance, in the photocatalytic selective transformation of hydrobenzoin, a benzaldehyde yield of about 91% is obtained using VO x /ZnO as the catalyst in methanol, while a benzoic acid yield of near to 99% can be achieved using a VO x or VO x /TiO2 catalyst in dichloromethane. Moreover, the oxidative cleavage of the C–C bonds of different substrates has also been investigated; 70.2–99.0% yields of the target products were obtained using the above-mentioned vanadium-based photocatalytic reaction systems.